Molecular events involved in the activation of calpain from human erythrocytes. Issue 2 (2004) - Dainese Dainese, Enrico Enrico; Sabatucci Sabatucci, Annalaura Annalaura; Minafra Minafra, Roberto Roberto; Vachette Vachette, Patrice Patrice; Melloni Melloni, Edon Edon; Cozzani Cozzani, Ivo Ivo
Abstract : Calpains are intracellular cysteine endopeptidases that combine protease activity with a dependence on Ca 2+ binding. Here we describe the conformational changes leading to the calpain activation, occurring in the enzyme purified from human erythrocytes, studied in solution using small angle X-ray scattering (SAXS). Addition of Ca 2+ determines the formation of large soluble aggregates that can be dissociated either chelating these ions or adding cahotropic salts in solution. On the other side, our SAXS studies revealed that the addition of Ca 2+ in the presence of inhibitors as E64 or leupeptin triggers a reversible conformational transition leading to a proper assembly of the active site without any aggregation or dissociation process. It is suggested that the observed conformational changes can be considered as the early step in the sequence of molecular events leading to calpain activation.